Analysis of Factors Increasing Creative Thinking in Vocational Education - Harianto, B.B; Pambudiyatno, Nyaris; Irfansyah, Ade (Indonesian Journal of Applied and Industrial Sciences (ESA), 2024)
Creative thinking is a crucial competency in vocational education, especially in facing the challenges of the dynamic aviation industry. This study aims to analyze the factors that influence the improvement of creative thinking skills of vocational education students at the Surabaya Aviation Polytechnic. This study uses a quantitative approach to analyze the relationship between variables, with a sample of 100 students taken using a simple random sampling technique from a population of 525 Vocational Education students at the Surabaya Aviation Polytechnic. Data were collected through questionnaires and then analyzed using Multiple Linear Regression using SPSS 22 software. The results showed that Intrinsic Motivation Factors, Innovative Teaching Method Factors, and Industry Support Factors had a significant influence on students' creative thinking skills, while Learning Environment Factors did not have a significant effect. The Adjusted R Square determination coefficient of 0.687 indicates that 68.7% of the variation in creative thinking skills can be explained by the independent variables in the model, with the remaining 31.3% explained by other factors outside the model.